HETEROGENEOUS REDUCTION OF URANYL BY MICAS: CRYSTAL CHEMICAL AND SOLUTION CONTROLS - Ilton E.S.; Haiduc A.; Moses C.O.; Heald S.M.; Elbert D.C.; Veblen D.R. (My University, 2004)
This contribution primarily uses X-ray photoelectron spectroscopy (XPS) to better understand mechanisms for coupled sorption-reduction of aqueous UVI by ferrous micas. Additional information was obtained with X-ray absorption spectroscopy (XAS) and transmission electron microscopy (TEM). The research is important because homogeneous reduction of aqueous UVI is sluggish compared to heterogeneous reduction pathways, and micas are important sorbents for uranium in granitic terrains, which have been proposed as potential radionuclide waste disposal sites.Three micas (high, medium and low Fe/Mg biotites), prepared as thin centimeter-sized books, were reacted with UVI solutions that contained 0–25 mM Na+ or K+, at pH = 4.5, 5.0, 6.0, and 9.5. All the experiments were performed under argon at one bar. Solid samples were retrieved at timed intervals for up to 20 h. Both mica edge and basal plane orientations were analyzed by XPS. Analyses of peak positions, core satellites, and the 5f valence band indicate that UVI can be reduced by biotite and that heterogeneous reduction depends on the type and concentration of alkali cation in solution, crystallography, and mica composition. We conclude that ferrous micas can reduce UVI on edge sites, but not on exposed basal plane surfaces, and that Na+ and K+ facilitate and hinder the reaction, respectively. These observations pertain over a broad range of pH.X-Ray absorption near edge spectroscopy (XANES) of annite sections indicates that the interlayer region, as opposed to external basal surfaces, also offers possible sites for heterogeneous reduction of UVI. TEM of annites with high uranium coverage confirmed the presence of interlayer uranium; interestingly, this uranium is concentrated in U-rich nano-scale zones.
Keywords: uranyl